THE IMPACT OF SEASON CHANGE AND ADAPTATION STRATEGIES OF MANAGEMENT AND LOCAL COMMUNITIES AROUND THE BALURAN NATIONAL PARK - Sylviani Sylviani; Niken Sakuntaladewi (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2010)
Climate change affects natural resources and the lives of communities particularly the ones whose living depends on the forest resources. They have to adapt to the existing change in order to survive. This research aims to picture the sectors affected by the climate change, its impacts to the communities particularly the ones who depends a lot on the environment tosurvive, and their adaptation strategies. The research is conducted to the local communities living in and around the Baluran National Park, Situbondo District, East Java Province. By using the methods of Risk Analysis degree of risk assessed and evaluated qualitatively as a consequence of the impacts of climate change on society. The research finds that local communities do not know about climate change, but they observe that there is a change in seasons. The rainy season becomes shorter and the dry season becomes longer. There is less water available to farm and to fulfill household needs and the temperature gets hotter. This condition provides negative impacts to agricultural sectors and fishery, the main sources of incomes of around 70% to 90% of the communities in the research area. It also provides negative impact to forestry sector, particularly in Baluran National Park, due to the increasing pressure to the park from the local communities to fulfill their needs of food, energy and family income. The community does adaptation in accordance with their potential, access to the surrounding natural resources, and development programs from the local government as well as the national park institute.Their adaptation is in the form of adjusting their planting season dan their planting pattern, finding other alternative sources to fulfill the family needs from the national park and development of other sectors, and development of wells, irrigation system, and dam. This adaptation can be classified into responsive and anticipative adaptation strategies. The local government and the National Park Institute work together to develop programs to respon the three needs of the local communities in order to keep the national park from further disturbance.